PENGARUH TRAUMA TERHADAP PRESTASI AKADEMIK SISWA SMP PASCA GEMPA DI KECAMATAN ALAS BARAT - Sumarni Larasati; Lukmanul Hakim; Roni Hartono (JURNAL PSIMAWA, 2019)
Trauma is one of the factors that can influence students academic achieviement. This research aims to know the influence of trauma on the academic achievement junior high school students after Earthquake in West Alas sub-district.This study apply a quantittative descriptive approach. The sampling technique apply Purposive Sampling, attracting by screening and determining the sample representatively using cluster sampling. The research sample consisted of 61 students grade VIII at SMPN 1 Alas Barat. The research data was obtained by using research instruments in the form of trauma scale and report value.The results of this study indicate that there is a significant influence of trauma for the academic achievement with the value of R Square of 0.230 with a significant value of 0.000<0.05. Based on the results of the study, generally trauma of grade VIII students of SMPN 1 Alas Barat in are in the medium category, which is 36.1%. The results of the study also showed that the academic achievement of class VIII students of SMPN 1 Alas Barat was included in the medium category of 34.4%. Trauma provides an effective contribution to the academic achievements of post-earthquake junior high school students in Alas Barat sub-district by 23% and 77% influenced by other factors outside of the research.